IMPLEMENTATION OF PERMA NUMBER 2 OF 2012 AND ITS RELEVANCE IN HANDLING THEFT CRIMINAL ACTIONS TO REALIZE SUBSTANTIVE JUSTICE (Case Study at Semarang Police) - David Putraningtyas, Agustinus; Purnawan, Amin (UNISSULA Semarang, 2023)
The research problem as follows: how the implementation of Perma Number 2 Year 2012 in handling criminal theft in Polres Semarang; How is the legal consequence of the criminal act of theft; What constraints arise in the implementation of Perma No. 2 of 2012. The result of the research concludes that Implementation of Perma Number 2 Year 2012 in handling criminal theft in Polres Semarang in this case has been applied as possible. The legal consequences in handling criminal theft in Polres Semarang to realize substantive justice based on Perma No. 2 of 2012 can be known from the cause of the failure of criminal justice in Polres Semarang because during the implementation of material criminal law is bound by formal legality as regulated in KUHAP. The obstacles are the limitations of Semarang Police personnel, budget, and investigation ability in conducting an investigation.Keywords: Implementation, Supreme Court Regulation, Theft Crime